INTERCULTURAL RELATIONS IN DAGESTAN: THE ROLE OF PERCEIVED SECURITY, INTERCULTURAL CONTACTS, AND MUTUAL ACCULTURATION - GALYAPINA, Victoria; LEPSHOKOVA, Zarina; MOLODIKOVA, Irina (CENTRAL ASIA AND THE CAUCASUS, 2021)
Dagestan is the most multiethnic and multilingual republic within the Russian Federation. From the viewpoint of interethnic relations, Dagestan is a unique research platform: the model of ethnopsychological compatibility of numerous peoples has been implemented here for centuries. It is essential for researchers to under- stand which factors contribute to and which hinder the establishment of effective interethnic communication in modern Dagestan. This empirical study was conducted in the context of the acculturation theory introduced by the Canadian cross-cultural psychologist John Berry. This article presents the results of researching the impact of perceived security, friendly intercultural contacts, preference for supporting a multicultural ideology, ethnic tolerance, and mutual integration attitude on the psychological well-being of both individual ethnic groups and Dagestani population as a whole.In the course of the study, the authors suggested that the higher the perceived security among ethnic groups in Dagestan, the greater the tendency towards maintaining a multicultural ideology, tolerance, and the preference for an integration strategy, and the lower the preference for a separation strategy (multiculturalism hypothesis). In addition, the authors hypothesized that the higher the intensity of friendly intercultural contacts between representatives of various ethnic groups in Dagestan, the higher their level of tolerance, preference for an integration strategy and the lower their preference for a separation strategy (contact hypothesis). The authors also suggested that the higher the preference for the integration strategy by representatives of various Dagestani ethnic groups, the higher their self esteem and life satisfaction (integration hypothesis). The sample included Avars, Dargins, Russians and representatives of other ethnic groups: Kumyks, Lezgins, Laks, Tabasarans, Nogais, etc. (total number of respondents N = 438).The data were analyzed both for the total sample and for a sample of specific ethnic groups using a Structural Equation Modeling (SEM) approach. MIRIPS questionnaire scales were used. The results demonstrated the contribution of perceived security to a preference for a multicultural ideology, tolerance, and mutual integration in the total sample. The results also demonstrated that the intensity of friendly intercultural contacts has no significant effect on tolerance or mutual integration in Dagestan. However, the preference for mutual integration contributes to life satisfaction and self-esteem among the in- habitants of Dagestan, which confirms the integration hypothesis. A separation prefer- ence was positively associated with perceived security, life satisfaction and negatively with friendly intercultural contacts among repre- sentatives of certain ethnic groups of Dages- tan. The results obtained demonstrate the importance of solving the problem of per- ceived security for building effective intercul- tural relations in Dagestan. The formation of a national policy in matters of preserving the cultural identity of various ethnic groups must be adequate, since, as the study has shown, separation strategy only leads to life satisfaction, and integration strategy is associated with both life satisfaction and self-esteem of the inhabitants of Dagestan.